Valoración, tratamiento y circulación de la información en los boletines institucionales (2004)
From the analysis of the content of 25 institutional bulletins of recognized public and private companies in Medellin, this paper points out the constant elements that makes this publication a fundamental scenario for the performance of the corporate communication professional with the purpose of spreading the official vision, also to align the public and to narrow the distance between the directive instances and other. Considering the assessment of the facts, the treatment and manipulation of the information, and the meanings put in circulation through this mean, it states that the idea is to make possible the objectives closely related to the political function in the organization, in which the professional appears as an invisible spokesman of the officialdom.